Shattered Dreams and the Return Home: Bangladeshi Migrant Workers in the Gulf Cooperation Council Countries During COVID-19 - Morad, Mohammad; Rabby, Al Amin; Sacchetto, Devi; Haque, Nadia (Two Homelands, 2023)
Since the onset of the COVID-19 pandemic, many Bangladeshi migrants have returned home, while many others are about to be repatriated. Drawing on qualitative research conducted with Bangladeshi migrants who returned from the Gulf Cooperation Council countries, this article analyzes the experiences of Bangladeshi laborers overseas during the pandemic to develop a better understanding of why these migrants returned to their home country. The main research questions here are twofold: How did COVID-19 affect the normal socioeconomic lives of Bangladeshi workers in the Gulf Cooperation Council, and to what extent is their return migration related to the COVID-19 pandemic?